2022
DOI: 10.1186/s12903-022-02242-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osseodensification on the increase in ridge thickness and the prevention of buccal peri-implant defects: an in vitro randomized split mouth pilot study

Abstract: Background Implant installation with conventional drilling can create buccal bone defects in areas of limited ridge thickness. Implant installation with osseodensification may aid in preventing buccal bone defects in these situations. This in vitro pilot study evaluated the impact of osseodensification on the increase in alveolar ridge thickness and the prevention of buccal peri-implant defects. Methods Ten fresh pig mandibles with limited bone thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, various authors focus on the techniques used for implant placement, highlighting that they condition the results obtained when evaluating the success rate and the osseointegration processes [ 25 , 26 , 27 ]. Different factors can influence: Temperature during drilling.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, various authors focus on the techniques used for implant placement, highlighting that they condition the results obtained when evaluating the success rate and the osseointegration processes [ 25 , 26 , 27 ]. Different factors can influence: Temperature during drilling.…”
Section: Discussionmentioning
confidence: 99%
“…However, if we consider OD, these materials are not the best choice for a real evaluation, as there is no collagen in the synthetic blocks, and it has been established that this is crucial for the technique [18]. Therefore, studies of OD carried out on synthetic blocks usually do not show the same results as ex vivo animal [18,19,28,29,42,47,64], in vivo animal [20][21][22][23][30][31][32][33] or clinical studies [24][25][26][34][35][36][37][38][39][40]53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary histologic findings from animal studies signify that osseodensification increases boneimplant contact (BIC) and bone-area fraction [5,7,10,11,[28][29][30][31][32]. Neiva et al [33] conducted human clinical trials and found that osseodensification crestal sinus floor elevation with chemically synthesized and biodegradable calcium phosphosilicate putty produced favorable and predictable results.…”
Section: Discussionmentioning
confidence: 99%